Csp3−H Activation without Chelation Assistance in an Iridium Pincer Complex Forming Cyclometallated Products. Issue 8 (16th January 2017) - Ahlstrand, David A.; Polukeev, Alexey V.; Marcos, Rocío; Ahlquist, Mårten S. G.; Wendt, Ola F.
Abstract: Cyclometallation of 8‐methylquinoline and 2‐(dimethylamino)‐pyridine in an iridium‐based pincer complex is described. The C−H activation of 2‐(dimethylamino)pyridine is not chelation assisted, which has not been described before for Csp 3 −H bonds in cyclometallation reactions. The mechanism of the cyclometallation of 2‐(dimethylamino)pyridine was studied by DFT calculations and kinetic measurements. Abstract : Help is not needed ! The C−H activation of 2‐(dimethylamino)pyridine is not chelation assisted, indicating that pre‐coordination may be less common in cyclometallation reactions than previously thought (see scheme).